Jesus according to Scripture restoring the portrait from the Gospels - Bock, Darrell L. (Grand Rapids, MI Baker Academic, 2002)
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- biography -- textbooks; Bible. N.T. Gospels -- textbooks